Strategi Kesantunan Berbahasa Netizen Dalam Kolom Komentar di Media Sosial (Instagram Presiden Prabowo) - Ningsih, Rika; Fatmawati, Fatmawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2026)
The development of social media as a public communication platform has generated diverse forms of linguistic interaction, including those occurring in the comment sections of official accounts belonging to public figures. However, the freedom of expression afforded by digital spaces is not always accompanied by the use of polite language. This study aims to analyze the linguistic politeness strategies employed by netizens in the Instagram comment section of President Prabowo's post commemorating International Workers' Day (Labour Day). A qualitative approach using content analysis was adopted in this study. The data consisted of netizens' comments, which were collected through documentation techniques and analyzed using Brown and Levinson's politeness strategy framework, encompassing bald on record, positive politeness, negative politeness, and off-record strategies. The findings reveal that, of the 986 comments analyzed, bald on record was the most dominant strategy, followed by off-record, negative politeness, and positive politeness. These findings indicate that netizens tend to employ direct strategies when expressing criticism on issues perceived as highly urgent, although other politeness strategies are also evident, reflecting efforts to maintain social relationships. Theoretically, this study reinforces the applicability of Brown and Levinson's politeness theory to digital political communication by demonstrating that the choice of politeness strategies is influenced by the social context and the nature of the issues being discussed. Practically, the findings provide valuable insights for promoting digital literacy and ethical public communication by encouraging the effective expression of criticism while maintaining linguistic politeness in online interactions. Overall, communication on social media reflects the complex dynamics of linguistic politeness, shaped by emotional, social, and digital contextual factors.